2021
DOI: 10.1186/s12967-021-02943-x
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei R3 protects against dextran sulfate sodium (DSS)-induced colitis in mice via regulating Th17/Treg cell balance

Abstract: Inflammatory bowel diseases (IBD), mainly comprising ulcerative colitis (UC) and Crohn's Disease, are most often a polygenic disorder with contributions from the intestinal microbiome, defects in barrier function, and dysregulated host responses to microbial stimulation. Strategies that target the microbiota have emerged as potential therapies and, of these, probiotics have gained the greatest attention. Herein, we isolated a strain of Lactobacillus paracasei R3 (L.p R3) with strong biofilm formation ability f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
1
27
1
Order By: Relevance
“…The mucophilic bacterium Akkermansia is a good example to protect the intestinal barrier by acetate and propionate production ( Hiippala et al, 2018 ). Unlike the results of other studies where strains alleviated DSS-induced colitis by a single effect ( Chen et al, 2015 ; Huang et al, 2021 ), we have demonstrated that the protective effect of L. acidophilus C4 for the repair of the intestinal mucous is achieved by relieving colon tissue damage, reducing the level of tissue inflammatory factors, and regulating the oxidative stress in mice. In addition, L. acidophilus C4 can maintain the homeostasis of the intestinal microenvironment by regulating the composition and abundance of the intestinal microbiota and the production of SCFAs.…”
Section: Discussioncontrasting
confidence: 99%
“…The mucophilic bacterium Akkermansia is a good example to protect the intestinal barrier by acetate and propionate production ( Hiippala et al, 2018 ). Unlike the results of other studies where strains alleviated DSS-induced colitis by a single effect ( Chen et al, 2015 ; Huang et al, 2021 ), we have demonstrated that the protective effect of L. acidophilus C4 for the repair of the intestinal mucous is achieved by relieving colon tissue damage, reducing the level of tissue inflammatory factors, and regulating the oxidative stress in mice. In addition, L. acidophilus C4 can maintain the homeostasis of the intestinal microenvironment by regulating the composition and abundance of the intestinal microbiota and the production of SCFAs.…”
Section: Discussioncontrasting
confidence: 99%
“…37,38 Inulin may promote Th17-type immune response by significantly upregulating ( p < 0.05) the abundance of Lactobacillus with Monoglobus to produce large amounts of SCFAs and significantly improving ( p < 0.05) nine disordered metabolic pathways. 40 Fucoidan is more similar to carrageenan in improving disordered metabolic pathways. Fucoidan exerts optimal metabolic disorder improvement by significantly inhibiting ( p < 0.05) all CTX immunosuppressive marker bacteria, significantly promoting the beneficial bacteria Rikenella , and significantly restoring ( p < 0.05) CD4/CD8 and upregulating TNF-α, IL-17, and IL-22.…”
Section: Discussionmentioning
confidence: 99%
“…The immune homeostasis of Th17/Treg plays a key role in host health and its disruption often induces autoimmune diseases, including IBD (Huang et al, 2021) and DM (Zhang et al, 2021b). Th17 cells are pro-inflammatory, secreting large amounts of IL-17A upon activation, causing damage to the colonic mucosa (Owaga et al, 2015), killing pancreatic β-cells and enhancing insulin tolerance (Kiernan & Maciver, 2020).…”
Section: Discussionmentioning
confidence: 99%